Deux frontières aux destins croisés ? Étude interdisciplinaire et comparative des délimitations territoriales entre la France et la Suisse, entre la Bourgogne et la Franche-Comté (xive-xxie siècle) - Castets Fontaine, Benjamin; Kaci, Maxime; Loiseau, Jérôme; Moine, Alexandre (Les Cahiers de la MSHE Ledoux, 2019)
This book is the result of interdisciplinary exchanges and brings together 16 international researchers to examine the links between territorial boundaries and the organization of societies. Following a comparative approach, the authors question, from the beginnings of modern states in the 14th century to today, the effects induced by the evolutions of these delimitations from two observation fields adjacent to each other: the territories between Burgundy and Franche-Comté where all boundaries seem to disappear; those between France and Switzerland where one of the last borders between France and a State that is not a member of the European Union is established. This comparison makes possible to determine what distinguishes a state border from territorial delimitations of other kinds.